HCV Management: Recent Updates - Rahman, Salimur (Bangladesh Journal of Medicine, 2023)
Background: Hepatitis C virus (HCV) has been a major public health threatboth worldwide and in Bangladesh due to itsconsiderable disease burden, morbidities, and death. An individualized, cost-effective, standard treatment regimen can help combat and eliminate HCV once and for all. Methods: This is an executive summary of the latest EASL (European Association for the Study of the Liver) recommendationsbased on existing literature, and clinical expertise from a panel of specialists chosen by the EASL Governing Board. Additionally, author’s clinical experience is undertaken for considering country level context. Results: HCV infection requires personalized treatment, based on factors such as genotype, liver fibrosis stage, and comorbidities. Direct-acting antiviral (DAA) regimens have replaced interferon, and are recommended as the first-line treatment for all patients with chronic HCV infection, irrespective of genotype. It is recommended to initiate treatment as soon as possible to prevent the progression of liver disease, and associated complications. For patients with decompensated cirrhosis, liver transplantation should be considered as a treatment option after weighing risk-benefit. Additionally, the management of special populations such as children, pregnant women, lactating mother, HCVpatients co-infected with HIV, HBV or SARS-CoV-2, patients with renal impairment, haemoglobin-opathies or bleeding disorders require special attention. Monitoring patients during and after treatment is recommended to ensure sustained virologic response (SVR), to detect any potential complication, and to check potential HCV reinfection. Conclusion: The EASL recommendations provide a comprehensive overview on personalized treatment of HCV, and monitoring for optimal patient outcomes, ushering high hopes for HCV elimination in the future. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 188